Evolution of Land Use Policy in Nepal - Sharma, Rabin K. (Journal on Geoinformatics, Nepal, 2012)
Land use is one of the priority sectors of Government of Nepal which can be visualized from the different official documents of the Government. In each of these documents, short term policy is introduced and most of the times it succeeded with partial implementation of the said policy. Therefore, this paper tried to review how the land use policies have been evolved from the period of eighth live year plan to date. Recently the council of ministers, Government of Nepal approved the Land Use Policy. The progress so far made in the preparation of land use data and maps have been briefly mentioned. Some of the key issues have been identified for not achieving the targeted goals of land use policy and proposed some suggestions to overcome the shortcomings. After the adoption of land use policy, it will effectively support in execution of land use implementation plan.